Pengaruh Return On Asset (Roa) Dan Earning Per Share (Eps) Terhadap Harga Saham Pada Pt. Bank Mandiri Persero Tbk Periode 2015-2024 - Dhita Amelia; Hestu Nugroho Warasto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to analyze the effect of Return on Assets (ROA) and Earnings per Share (EPS) on the stock price of PT Bank Mandiri (Persero) Tbk during the 2015–2024 period. The research employs a quantitative approach with an associative research design. The data used are secondary data obtained from annual financial statements and closing stock prices published by the Bursa Efek Indonesia. The analytical methods include descriptive statistical analysis, classical assumption tests, simple and multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing using t-tests and F-tests with SPSS version 29.The results indicate that partially, ROA does not have a significant effect on stock prices (t-count -0.867 < t-table 2.306; significance 0.411 > 0.05). Similarly, EPS does not have a significant partial effect on stock prices (t-count 1.444 < t-table 2.306; significance 0.187 > 0.05). Simultaneously, ROA and EPS also do not significantly affect stock prices (F-count 4.665 < F-table 4.737; significance 0.052 > 0.05). The Adjusted R Square value of 0.449 indicates that 44.9% of stock price variation is explained by ROA and EPS, while the remaining 55.1% is influenced by other factors outside the research model.